[C(NH2)3]2S2O8: combining delocalized and localized π-conjugate units to achieve strong optical anisotropy. Issue 23 (12th October 2022) - Zhang, Man; Zhang, Bingbing; Yang, Daqing; Wang, Ying
Abstract : The optimizing combination of organic delocalized π-conjugated units and inorganic structural units with localized π orbitals leads to large birefringence and short UV cut-off edge. Abstract : A new birefringent crystal [C(NH2 )3 ]2 S2 O8 was obtained by combining the π-conjugated [C(NH2 )3 ] cation and the [S2 O8 ] groups with localized O–O π-bonds. Optical measurements show that the UV cutoff wavelength of [C(NH2 )3 ]2 S2 O8 is 222 nm, and its birefringence is 0.102 at 546 nm. The calculated results show that its large birefringence is attributed to the synergistic effect of the [C(NH2 )3 ] and [S2 O8 ] units, which is the first case among known birefringent crystals. These results provide new insights into the design of superior birefringent materials.